2011
DOI: 10.5402/2011/920753
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of Coordinated Ni(II) Complex with High Nitrogen Content Ligands

Abstract: Density functional computations were performed on two tetracoordinated Ni(II) complexes as high nitrogen content energetic materials (1: dinickel bishydrazine ter[(1H-Tetrazol-3-yl)methan-3yl]-1H-tetrazole and 2: dinickel tetraazide ter[(1H-Tetrazol-3-yl)methan-3yl]-1H-tetrazolate). The geometrical structures, relative stabilities and sensitivities, and thermodynamic properties of the complexes were investigated. The energy gaps of frontier molecular orbital (HOMO and LUMO) and vibrational spectroscopies were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…All optimized systems correspond to a minimum without negative frequencies. The interatomic distances obtained in this study are closely related except for those of [PdL 1 (H 2 O)Cl] and [PdL 2 (H 2 O)Cl] with metal–ligands interatomic distance of 1.96 Å. Interatomic distances reported in this work are comparable to those reported in our previous work and in the literature …”
Section: Resultssupporting
confidence: 88%
“…All optimized systems correspond to a minimum without negative frequencies. The interatomic distances obtained in this study are closely related except for those of [PdL 1 (H 2 O)Cl] and [PdL 2 (H 2 O)Cl] with metal–ligands interatomic distance of 1.96 Å. Interatomic distances reported in this work are comparable to those reported in our previous work and in the literature …”
Section: Resultssupporting
confidence: 88%
“…From the present study, it was found that coordination complexes can be prepared from the direct metal than their salts. The experiments in computer-aided chemistry use mathematical models derived from computational chemistry to calculate molecular properties and geometries [25]. According to best of our knowledge the reported crystal structure are essentially the same as the structure described by us but previously reported crystal structure showed more positional disorder for the carbon atoms.…”
Section: Introductionmentioning
confidence: 55%
“…The coordination bond lengths and angles of 1 are summarized in Table 2 , which indicates the nearly ideal octahedral coordination geometry around the Ni center, with minor deviations. The Ni–N bond lengths are in the range of 2.039(5)–2.095(5) Å, which are typical for Ni II –N(imine) coordination bonds [ 33 , 34 ]. The five-membered chelate bite angles (N1–Ni1–N2 and N6–Ni1–N7) are smaller by ca.…”
Section: Resultsmentioning
confidence: 99%